2020
DOI: 10.3389/fvets.2020.00226
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical Pulmonary Cytokine Profiles Are Linked to Bronchoalveolar Lavage Fluid Cytology of Horses With Mild Airway Neutrophilia

Abstract: Few data on cytokine profiles in bronchoalveolar lavage fluid (BALF) are available for racehorses with mild/moderate equine asthma (EA); cytological diagnosis being most frequently made from only one lung. The purpose of the study was to compare cytokine mRNA expressions and protein concentrations in BALF from both lungs. As part of a larger study, 250 ml saline was randomly instilled in one lung and 500 ml in the contralateral lung of 30 clinically healthy Standardbred racehorses. This procedure was repeated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Studies suggest that excessive immune response is involved in the formation of RMPP, and CCL2 is involved in the immune response. Hue Erika et al [ 37 ] found in an animal experiment that the level of cytokines in the bronchoalveolar lavage fluid (BALF) of the affected side was significantly higher than that of the healthy side. It has a higher predictive value than CRP and LDH in predicting the occurrence of RMPP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies suggest that excessive immune response is involved in the formation of RMPP, and CCL2 is involved in the immune response. Hue Erika et al [ 37 ] found in an animal experiment that the level of cytokines in the bronchoalveolar lavage fluid (BALF) of the affected side was significantly higher than that of the healthy side. It has a higher predictive value than CRP and LDH in predicting the occurrence of RMPP.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with serum markers, the changes of biomarkers in BALF have higher specificity and sensitivity, and can indicate the progression of lung diseases earlier and more accurately. In an animal study, Hue Erika et al [ 19 ] found that the cytokine levels in bronchoalveolar lavage fluid (BALF) of the affected side were significantly higher than those in the healthy side, possibly due to further lung injury caused by excessive activation of immune cells. The strong local inflammatory response of MPP suggests that the chemokines in BALF may be more meaningful for the prediction of RMPP.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike human asthma, the term ‘severe’ for EA is used to describe a greater degree of lower airway inflammation and severity of clinical signs but does not necessarily mean the asthma is difficult to manage or treat. Equine asthma is a chronic inflammatory lung disease with characteristics similar to human asthma, including enhanced bronchial reactivity; chronic, partially reversible airflow obstruction; pulmonary remodeling; lower airway inflammation [ 224 , 225 , 226 ]. Equine asthma prevalence is not clearly defined, but some studies suggest that up to 80% of horses may have mEA and up to 17% may have sEA [ 227 , 228 , 229 , 230 , 231 ].…”
Section: Naturally Occurring Animal Models Of Asthmamentioning
confidence: 99%
“…While mouse models of neutrophilic asthma are now available [ 270 ], and have been used to identify novel biomarkers and therapeutic approaches [ 271 , 272 ], horses are another potentially useful translational model for this important asthma endotype. Like asthma in humans, sEA is a chronic disease that leads to structural changes in the lung that mirror changes in humans with asthma [ 225 , 273 ]. With environmental management, asthmatic horses can be maintained in remission and exacerbation can be induced when needed by feeding dusty/moldy hay or nebulizing hay dust extract (HDE).…”
Section: Naturally Occurring Animal Models Of Asthmamentioning
confidence: 99%
“…In studies of asthmatic horses, these endotypes have been identified in both EA phenotypes, mEA and sEA, suggesting classification systems other than mEA and sEA may be needed to describe underlying disease immunopathology (8). The cytokine profiles of mEA and sEA, either at the protein or mRNA level, may support a type 1, type 2, type 17, or mixed immune response, depending on the study (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Inconsistencies in reported cytokine profiles and subcategorizing EA based on clinical severity rather than immune characteristics of the disease have limited ability to fully describe the pathogenesis of EA and establish clinically relevant disease categories, which ultimately limits diagnostic, treatment, and management abilities.…”
Section: Introductionmentioning
confidence: 99%